Terapi Psikoedukasi terhadap Self Care Activity pada Penderita Diabetes Mellitus - Argi Virgona Bangun; Fitria Ningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the difference in the mean before and after the implementation of psychoeducation therapy on self-care activities in diabetes mellitus sufferers in RW 07 in the work area of Puskesmas Cimahi Tengah. The method in this study used a pre-experiment, with a one group pretest-posttest research design. The sample in this study were patients with type 2 diabetes millitus. This study used a consecutive sampling of 11 respondents. Psychoeducation therapy was given for 5 meetings in 21 days and measurement of self-care activity using the SDSCA questionnaire, then the data were processed using univariate analysis (mean, SD, 95% CI, and Min-Max) and bivariate (t-dependent test). The pretest results obtained were 10.63 and the posttest was 23.00 and the Pvalue was 0.001. In conclusion, there is an effect of psychoeducation therapy on self-care activity in diabetes mellitus sufferers. Keywords: Diabetes Millitus, Psychoeducation, Self-Care Activity